Proverbs, Charms and Religious Folktales: A Dialogue of Genres - Katrinaki, Emmanouela; Tserpes, Georgios (Tautosakos darbai, 2026)
The phenomenon of some short folklore genres being included in broader folktales is quite frequent. In this paper we examine the relationship between proverbs, a particular charm, and two religious folktales from older folkloristic sources, mainly from the first half of the 20th century, and contemporary online conversations in a Facebook group with the title Κρητική διάλεκτος – ντοπιολαλιά (Cretan dialect – vernacular). In this group, participants ask questions about the meaning of words and phrases. In our case studies these phrases belong to broader traditional tales; in the discussion about their meaning, group members attempt to interpret them through a process of oral literary criticism. In doing so, they produce new variations of well-known traditional tales. From this examination, we aim to find how proverbs and charms function in the texts studied and how they adapt to new contexts.
Keywords: genre; charms; proverbs; folktales; ATU; oral literary criticism